1999
DOI: 10.1037/0278-7393.25.2.488
|View full text |Cite
|
Sign up to set email alerts
|

When unfamiliarity matters: Changing environmental context between study and test affects recognition memory for unfamiliar stimuli.

Abstract: Performance in recognition memory has been shown to be relatively insensitive to the effect of environmental context changes between study and test. Recent evidence (P. Dalton, 1993) showed that environmental context changes between study and test affected recognition memory discrimination for unfamiliar stimuli (faces). The present study presented 2 experiments that replicated this finding, refined the experimental methodology, and extended the findings to unfamiliar verbal material (nonwords). Finally, a 3rd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 35 publications
6
42
1
Order By: Relevance
“…First of all, there is a clear trend toward the appearance of place-context-dependent recognition being influenced by the familiarity or meaningfulness of the materials. It has been repeatedly reported that the recognition of unfamiliar or meaningless materials, such as unfamiliar faces and nonwords, is influenced by changes in place context (e.g., Dalton, 1993;Malpass & Devine, 1981;Russo, Ward, Geurts, & Scheres, 1999). For instance, Dalton found place-context-dependent recognition of unfamiliar faces; Russo et al successfully replicated the place-context-dependent recognition of unfamiliar faces, and further found context-dependent recognition with nonwords but not with meaningful words.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…First of all, there is a clear trend toward the appearance of place-context-dependent recognition being influenced by the familiarity or meaningfulness of the materials. It has been repeatedly reported that the recognition of unfamiliar or meaningless materials, such as unfamiliar faces and nonwords, is influenced by changes in place context (e.g., Dalton, 1993;Malpass & Devine, 1981;Russo, Ward, Geurts, & Scheres, 1999). For instance, Dalton found place-context-dependent recognition of unfamiliar faces; Russo et al successfully replicated the place-context-dependent recognition of unfamiliar faces, and further found context-dependent recognition with nonwords but not with meaningful words.…”
supporting
confidence: 55%
“…A trend for the effect size to decrease with greater familiarity and meaningfulness can be found in previous studies. In particular, Russo et al (1999) found significant context-dependent recognition with nonwords but not with words. They compared the influences on words and nonwords within one study but in separate experiments, and used an incidental-learning paradigm.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Clark & Gronrund, 1996)ῌ ̰ΰῳῤῧQQ ῦ̮̮ῡ´῎ῷ̲̲ΰ̯QQ̳Ύῦ῎QΊ`̲ ῲQ ΅QῳῢῨ̮`Ὺῧῧῌ QQΎ̲ ῧῬ̮ῥQῴΎ̲ ῧQQQ̮ΏQ̲ΰΊῡ̮̯ (cf. Clark & Gronrund, 1996) (Dougal & Rotello, 1999;Murnane & Phelps, 1993, 1994, 1995Murnane et al, 1999) (Smith, 1988(Smith, , 1994)῍ ῙῙῡῌ Q̮̮΅ῦQῚῧῌ Q̮̮΅Qῥ̰̰῝`ῢῲ ῠ` (Watkins & Watkins, 1975) Dalton, 1993;Q̯ , 1991;Russo, Ward, Geurts, & Scheres, 1999;Smith, 1986ῐ῎ (Dougal & Rotello, 1999;Murnane & Phelps, 1993, 1995Murnane et al, 1999) (Dougal & Rotello, 1999;Murnane & Phelps, 1993, 1995Murnane et al, 1999) (Dougal & Rotello, 1999;Murnane & Phelps, 1993, 1995Murnane et al, 1999) (Dougal & Rotello, 1999;Murnane & Phelps, 1995) ῡQ̮̯Ί῭ῠ̮Ῥ῍ Ὶ῭ῥ̮ ῠῌ QῨῥ̮̰̰῞QQῳῶῦQ̳`ΊῨ̯QQῡῧῌ ̯ῦ̮῟῭̰̮ῳῶ̱Ώῲ̲ Q`QQῠ̮Ῥ ῒe.g., Dalton, 1993;Q̯ῌ 1991;Russo et al, 1999;Smith, 1986ΐ῍ ̰QQῳῶ̰ῗQQQῳῶῦ̰̮ῥῌ ̱̲Ὸῼῑῴ̱Ὼ̲ῲῦ̲̯ῤῚ`῏Q̯ῳῶ ῢῌ QQῌ ῦ̮ῌ BGM ῦ̰̮ῥῌ ῧQ̯QQῥQ῞ Ῥῳῶῦ̮῟῭̰̮QQ̯ῳῶῥῲ̲Ί῭ῠ̮Ῥ̮ (e.g., Smith, 1988)ῌ ̯ῦQQῥῧQῐῦῐ̯̮Q ῞ῬῚῢ̮̱QΊ῭ῠ̮Ῥ῍ ̰QQῳῶ̰ῗQQQῳῶ ῧῌ Q̮̮Ύ΅̳̮QῘῤῬῢῌ QῨ̱̱QΎῡῧῳῶ Q̳̮Q῝ῤῘῤῬ̮ ῒῴQQ῏ Dougal & Rotello, 1999;Murnane & Phelps, 1993, 1995Murnane et al, 1999ΐῌ ̯ῦ̰̮ῤQ̮Q̮̮Ύ΅̳QQῡ̰ῌ Q QῳῶῡῧῺ῾ῤῳῶQ̳̮Q῝Ῥ (Canas & Nelson, 1986;…”
mentioning
confidence: 99%
“…Though some researchers have demonstrated that unfamiliarity matters (Russo, Ward, Geurts, & Scheres, 1999), it could be that there are affects from familiarity also. It is possible that familiarity might lead to quicker and presumably more accurate judgement based on the familiarity (though rushing to a decision was also possible, leading to error).…”
Section: Famementioning
confidence: 99%